2022
DOI: 10.1128/spectrum.02572-21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of OXA-232-Producing Carbapenem-Resistant Klebsiella pneumoniae Strains Isolated during Nosocomial Clonal Spread Associated with Environmental Colonization

Abstract: OXA-232 is a variant of OXA-48 carbapenemase, which has been increasingly reported in nosocomial outbreaks in ICUs. However, the OXA-232-CRKP transmission relationship between the environment and patients in ICUs was still not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Furthermore, we observed the evolution of carbapenem-resistance plasmids during the clonal spread of CRKP. Notably, our previously reported study revealed a correlation between long-term colonization and the risk of further infection ( 30 ). Considering these findings, we strongly recommend the implementation of regular surveillance measures for CRKP in both patient and environmental settings.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we observed the evolution of carbapenem-resistance plasmids during the clonal spread of CRKP. Notably, our previously reported study revealed a correlation between long-term colonization and the risk of further infection ( 30 ). Considering these findings, we strongly recommend the implementation of regular surveillance measures for CRKP in both patient and environmental settings.…”
Section: Discussionmentioning
confidence: 89%
“…From 1 August to 31 December 2019, a CRKP screening program was performed in the ward environments and patients in the ICU in Sir Run Run Shaw Hospital (Zhejiang Province, China), as reported before ( 30 ). Briefly, the patient’s anatomic sites for sampling included rectal swab, nasointestinal tube, nasogastric tube, oral swab, tracheotomy tube, and endotracheal intubation.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous monitoring of the decreasing susceptibility of multidrug-resistant bacteria to disinfectants helps to effectively control and prevent the spread of superresistant bacteria. Our previous study revealed that the detected CRKP carried disinfectant resistance genes and virulence clusters and recommended the appropriate use of disinfectants to prevent the development of resistance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prevalent carbapenemase genes, bla OXA-48 (oxacillin-hydrolyzing β-lactamase), is found predominantly on large and transferable plasmids in bacteria of order Enterobacterales. Prevalence of K. pneumoniae strains carrying a bla OXA-48 –like gene in China increased during 2018–2022 ( 3 6 ). Nosocomial outbreaks, including among pediatric patients, have called attention to the importance of better understanding the transmission potential of CRKP isolates carrying the bla OXA-48 –like gene ( 4 6 ).…”
mentioning
confidence: 99%
“…Prevalence of K. pneumoniae strains carrying a bla OXA-48 –like gene in China increased during 2018–2022 ( 3 6 ). Nosocomial outbreaks, including among pediatric patients, have called attention to the importance of better understanding the transmission potential of CRKP isolates carrying the bla OXA-48 –like gene ( 4 6 ).…”
mentioning
confidence: 99%